Concentrations of Heavy Metals in Soil of West Qurna-1Oilfield Northern Basrah - Ghanem, Abdullah M.; Issa, Murtadha Jabbar (Iraqi Journal of Science, 2025)
The current experiment set out to determine the level of heavy metal pollution in the studied soil. Sixteen sites were chosen to collect soil samples. ICP-MS was utilized to assess heavy metals in soil samples. The detected heavy metal concentrations were compared with the values of the Geochemical Background WHO recommendations. Based on the pH values, all soil samples in the research region are determined to be alkaline. The average pH of the research area is 7.30. The heavy metal pollution was evaluated using descriptive statistical analysis and a correlation matrix. The soil exhibits a range of heavy metal pollution, varying from very low to severe. The mean concentration of elements B, Cu, Hg, Cr, Ni, and Sr was higher than the global soil concentration. The Co level of pollution was moderate. The pollution levels of Ce, Zn, V, Ba, and As in the world soil were lower. Unlike the global average percentage of contaminated soil, the remaining elements exhibited lower pollution levels.